Level of Satisfaction with the School-Based Management Process: Basis for Improved Management System - Mark Anthony Pasubillo; John Mark Asio (Journal of Elementary and Secondary School, 2023)
In instructional management styles and strategies, parents observe teachers and administration employed in an academic community. They must align the values parents expect from their children. As study participants, parents understand that the school administration must demonstrate academic excellence. This study aims to determine the level of satisfaction with the school-based management of stakeholders in a regional science high school in Olongapo City, Philippines. The stakeholders' level of satisfaction is measured through the four (4) major areas of school-based management: leadership and governance, curriculum and instruction, accountability and continuous improvement, and management and resources. The study employed a descriptive survey research method with the help of a survey questionnaire as the primary data-gathering tool. One hundred ninety (190) stakeholders voluntarily participated and responded to the call with the help of the purposive sampling technique. The researchers developed an instrument that underwent validity and reliability evaluation. The study also used descriptive and inferential statistics to assess the gathered data. The study revealed that the stakeholders were "very satisfied" regarding curriculum and instruction, accountability and continuous improvement, and management and resources. However, only leadership and governance yielded "satisfied" stakeholder remarks. Furthermore, there were no substantial differences in the school-based management satisfaction of the stakeholders when grouped according to their profiles. Based on the results, the researchers recommended some vital suggestions at the end of the study.